Sífilis congênita : análise espacial e aspectos epidemiológicos das mães - Cruz, Verena Cardoso (2019)
Introduction: Syphilis is a sexually transmitted infection that can also be transmitted parenterally or transplacentally. Because of syphilis in pregnant women, the number of congenital syphilis cases has increased, especially in the northern and northeastern regions of Brazil. Objective: To analyze the occurrence of congenital syphilis in the state of Sergipe from 2007 to 2017.Methodological: This is an ecological study regarding all cases of congenital syphilis residing in the state of Sergipe. Data were obtained from the Notification Disease Information System (SINAN) and the Brazilian Institute of Geography and Statistics (IBGE). For spatial analysis we used: a) the local empirical Bayesian model for rate smoothing; b) Moran Global statistics with pseudo-significance test to examine spatial dependence. Results: The mothers of the children with syphilis were young with a high proportion of adolescents, with low education, paid work and coming from the urban area. Most prenatal patients were not diagnosed with syphilis and were in the latent phase of the disease, received inadequate treatment, their partners were not treated, contributing to the high incidence of congenital syphilis, identified by the progressive increase over the 11 years studied. The central and southern areas of the state of Sergipe presented the highest incidence rate corrected by the model local empirical Bayesian and the municipalities identified as priorities were: Divina Pastora, Siriri e Maruim. Conclusion: There is a need for permanent education to perceive vulnerability, active search for prenatal and effective screening of syphilis in pregnant women with appropriate treatment establishment.